Characteristic of kombucha tea concentrate purified through stirred microfiltration cell (Smfc) from local green tea (Camellia sinensis (L.) O. Kuntze) as functional drink for relaxation - Susilowati, Agustine (Research Institute for Tea and Cinchona, 2016)
L-theanine is amino acid contained in tea (Camellia sp.) leaves having ability as relaxation compound. Combination of L-theanine and other compounds produced from fermentation of green tea extract by Kombucha starter generates Kombucha tea with unique taste and better relaxation functional. The concentrate of Kombucha tea as functional drink for relaxation (anti stress) was produced by purification on fermented green te extract through 0.2 µm MF membrane fitted in stirred microfiltration cell (SMFC) at stirrer rotation speed of 200 rpm and 400 rpm, and pressure of 30 psia. Purification was conducted on 4 grades of Kombucha tea from local green tea extract with rich L-theanine, such as Pekoe, Dewata, Arraca Kiara and Arraca Yabukita as a result of purification by MF module. Kombucha tea produced through fermentation at 1 part of permeate and 1 part of water ratio using Kombucha (5%, v/v) starter riched by sucrose of 10% (w/v) under room temperature for 7 days. Based on the best L-theanine concentration, the result of experiment showed that SMFC at stirrer rotation speed of 400 rpm was able to retain L-theanine in retentate from Kombucha tea of Arraca Kiara, Arraca Yabukita, Dewata, and Pekoe grades, subsequent 29.1, 96,53, 44.62 and 71.54% (w/v) from prior to process as feed. In other words, optimization condition was reached at Kombucha tea of Arraca Yabukita grade producing retentate or concentrate of Kombucha tea with L-theanine, total polyphenol, reducing sugar, total solids, and total of titratable acids of 2.5605% (w/w), 3.4314% (w/w), 14 mg/mL, 4.8947% (w/w), and 0.2195% (v/v) respectively.